THE ROLE OF LOANWORDS IN MODERN RUSSIAN LANGUAGE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores borrowed words in the Russian language, their origin, adaptation to orthographic and phonetic norms, and common difficulties in their usage. Based on the analysis of examples from modern speech and written sources, the paper identifies the most frequent spelling and pronunciation mistakes. A classification of borrowings by source and degree of assimilation is provided.